Hubungan Empati Dengan Perilaku Konflik Dengan Orang Tua Dual-Career - Humbaina, Mutia; Rizkyanti, Charyna Ayu (Universitas Islam Negeri Raden Intan Lampung, 2020)
The aim of this study is to determine the relationship of empathy and conflict behavior in early adolescents who have dual-career parents. There were two instruments: The Basic Empathy Scale (BES) by Jolliffe and Farrington (2006 and Conflict Behavior Questionnaire (CBQ) by Robin & Foster (1989). A total respondents of this study were 252 adolescents (N male = 95; N female = 157) obtained online through self-selected polls. By the Spearman's Product Moment correlation analysis, the results showed that there was a significant negative between empathy and conflict behavior in early adolescents with dual-career parents (r = -0,277 p <0.05). The results also showed that there were significant differences in conflict behavior between ages 13 years to 16 years, where the age of 14 years was higher (M = 152.83) in experiencing conflict behavior compared to other ages. The implication of this research highlighted the importance of developing empathy in adolescents as an effort to minimize conflict with parents.